The generation and amplification of intergalactic magnetic fields in analogue laboratory experiments with high power lasers - Gregori, G; Reville, B; Miniati, F (Elsevier, 2015)
The advent of high-power laser facilities has, in the past two decades, opened a new field of research where astrophysical environments can be scaled down to laboratory dimensions, while preserving the essential physics. This is due to the invariance of the equations of magneto-hydrodynamics to a class of similarity transformations. Here we review the relevant scaling relations and their application in laboratory astrophysics experiments with a focus on the generation and amplification of magnetic fields at cosmological shock waves. These arise during the collapse of protogalactic structures, resulting in the formation of high Mach number shocks in the intergalactic medium, which act as sources of vorticity in protogalaxies. The standard model for the origin of magnetic fields is via baroclinic generation from the resulting misaligned pressure and temperature gradients (the so-called Biermann battery process). While both experiment and numerical simulation have confirmed the occurrence of this mechanism at shocks, reconciling the resulting weak fields with present day observations is an un-solved problem, although it is generally accepted that turbulent motions of the weakly magnetised plasma plays a key role. Bridging the vast scale differences is a challenge both numerically and experimentally. A summary of novel laboratory experiments aimed at investigating additional processes that may shed light on these and other processes, such us turbulent amplification, resistive and collision-less plasma instabilities will be discussed in this review, particularly in relation to experiments using high power laser systems. The connection between laboratory shock waves and additional mechanisms, such as diffusive shock acceleration will be discussed. Finally, we will summarize the impact of laboratory investigation in furthering our understanding of plasma physics on super-galactic scales.